2020
DOI: 10.1002/bsl.2487
|View full text |Cite
|
Sign up to set email alerts
|

Detecting children's true and false denials of wrongdoing: Effects of question type and base rate knowledge

Abstract: One common and unfortunately overlooked obstacle to the detection of sexual abuse is non-disclosure by children. Non-disclosure in forensic interviews may be expressed via concealment in response to recall questions or via active denials in response to recognition (e.g., yes/no) questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…This influence has been shown specifically in the case of evaluating the accuracy of the accounts of others. This work has shown that giving participants information about prior probabilities (e.g., telling them that of the statements they will hear 50% will be true and the other 50% will be false) does change their evaluations of the statements of others, specifically by decreasing the presence of ‘truth bias’, where people tend to believe others are telling the truth more often than they actually are, despite not increasing the accuracy of evaluations (Domagalski et al, 2020; Kassin et al, 2005). Thus, prior probabilities may be playing a role in interpretations of evidence, although their influence is unlikely to be statistically correct in a Bayesian sense (see also Smith et al, 1996 on juror use of probabilistic evidence).…”
Section: Introductionmentioning
confidence: 99%
“…This influence has been shown specifically in the case of evaluating the accuracy of the accounts of others. This work has shown that giving participants information about prior probabilities (e.g., telling them that of the statements they will hear 50% will be true and the other 50% will be false) does change their evaluations of the statements of others, specifically by decreasing the presence of ‘truth bias’, where people tend to believe others are telling the truth more often than they actually are, despite not increasing the accuracy of evaluations (Domagalski et al, 2020; Kassin et al, 2005). Thus, prior probabilities may be playing a role in interpretations of evidence, although their influence is unlikely to be statistically correct in a Bayesian sense (see also Smith et al, 1996 on juror use of probabilistic evidence).…”
Section: Introductionmentioning
confidence: 99%
“…11 14 Unfortunately, lessons from the past make us aware that the use of developed tools to facilitate disclosure, such as dolls and diagrams, even by professionals, can lead to false positive results. [18][19][20] This can have major consequences, especially if such findings are used during the legal process, as was shown in notorious cases of false allegations of CSA. [21][22][23][24] The current lack of scientific substantiation and the risk of improper tool use emphasise the importance of developing reliable, structured, evidence-based and uniform methods to support the diagnosis of CSA in clinical practice.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The limited verbal capacity of young children may hamper their ability to express their experiences, thoughts and feelings even more 11 14. Unfortunately, lessons from the past make us aware that the use of developed tools to facilitate disclosure, such as dolls and diagrams, even by professionals, can lead to false positive results 18–20. This can have major consequences, especially if such findings are used during the legal process, as was shown in notorious cases of false allegations of CSA 21–24.…”
Section: Introductionmentioning
confidence: 99%
“…Adults are poor at accurately detecting deception in children, with studies reporting that adults perform slightly above chance levels (Domagalski et al., 2020; Edelstein et al., 2006; Gongola et al., 2017; Talwar et al., 2009; Wyman et al., 2019). A meta‐analysis revealed that adults' accuracy rates for detecting deception in children were around 47.5% (Gongola et al., 2017).…”
mentioning
confidence: 99%
“…A meta‐analysis revealed that adults' accuracy rates for detecting deception in children were around 47.5% (Gongola et al., 2017). Adults have a tendency to exhibit a truth bias by taking reports at face value and believing child senders (Bond & DePaulo, 2006; Domagalski et al., 2020; Vrij et al., 2010). Moreover, police officers are generally no better than laypeople at accurately detecting deception in children (Leach et al., 2004; Vrij et al., 2006).…”
mentioning
confidence: 99%